Analysis of NFKB1 and NFKB2 gene expression in the blood of patients with sudden sensorineural hearing loss. (March 2023) - Jabbari Moghadam, Yalda; Asadi, Mohammad Reza; Abbaszadeh, Vahdat; Gharesouran, Jalal; Dehghani, Hossein; Sabaie, Hani; Hussen, Bashdar Mahmud; Taheri, Mohammad; Akbari Dilmaghnai, Nader; Rezazadeh, Maryam
Abstract: Objectives: Sudden Sensorineural Hearing Loss (SSNHL) is an increasingly common health problem today. Although the direct mortality rate of this disorder is relatively low, its impact on quality of life is enormous; this is why accurate identification of pathogenesis and influencing factors in the disease process can play an essential role in preventing and treating the disease. Acute inflammation, which leads to chronic inflammation due to aberrant expression of inflammation-mediating genes, may play a significant role in the pathogenesis of the disease. The essential Nuclear factor kappa B (NF-kB) pathway genes, NFKB1 and NFKB2, serve as prothrombotic agents when expressed abnormally, compromising the cochlea by disrupting the endolymphatic potential and causing SSNHL. Methods: This study investigates the expression levels of NFKB1 and NFKB2 in peripheral blood (PB) through a quantitative polymerase chain reaction in 50 Iranian patients with SSNHL, and 50 healthy volunteers were of the same age and sex as controls. Results: As a result, NFKB2 expression levels in patients were higher than in controls, regardless of sex or age (posterior beta = 0.619, adjusted P-value = 0.016), and NFKB1 expression levels did not show significant differences between patients and controls. The expression levels of NFKB1 and NFKB2 had significantly strong positive correlations in both SSNHL patients and healthy individuals (r = 0.620, P = 0.001 and r = 0.657, P 0.001, respectively), suggesting the presence of an interconnected network. Conclusion: NFKB2 has been identified as a significant inflammatory factor in the pathophysiology of SSNHL disease. Inflammation can play an essential role in developing SSNHL, and our findings could be used as a guide for future research.